2000
DOI: 10.1038/79759
|View full text |Cite
|
Sign up to set email alerts
|

Identification of complement factor 5 as a susceptibility locus for experimental allergic asthma

Abstract: The prevalence and severity of allergic asthma continue to rise, lending urgency to the search for environmental triggers and genetic substrates. Using microarray analysis of pulmonary gene expression and single nucleotide polymorphism-based genotyping, combined with quantitative trait locus analysis, we identified the gene encoding complement factor 5 (C5) as a susceptibility locus for allergen-induced airway hyperresponsiveness in a murine model of asthma. A deletion in the coding sequence of C5 leads to C5-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
258
3
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 356 publications
(279 citation statements)
references
References 43 publications
17
258
3
1
Order By: Relevance
“…This contention is consistent with previous studies showing that C5a can induce Th1 responses through its ability to enhance IL-12 production in APCs (25,31). Although there is no direct evidence that C5aR blockade leads to an enhancement of Th2 priming by a lack of counterbalancing IL-12 production by mDCs in vivo, Gavett and colleagues (32) have previously shown that administration of rIL-12 to C5-deficient A/J mice suppressed allergen-induced AHR concomitant with a reduction in Th2 cytokine production.…”
Section: Role Of C5/c5a In Regulating Adaptive Immune Response To Allsupporting
confidence: 82%
See 1 more Smart Citation
“…This contention is consistent with previous studies showing that C5a can induce Th1 responses through its ability to enhance IL-12 production in APCs (25,31). Although there is no direct evidence that C5aR blockade leads to an enhancement of Th2 priming by a lack of counterbalancing IL-12 production by mDCs in vivo, Gavett and colleagues (32) have previously shown that administration of rIL-12 to C5-deficient A/J mice suppressed allergen-induced AHR concomitant with a reduction in Th2 cytokine production.…”
Section: Role Of C5/c5a In Regulating Adaptive Immune Response To Allsupporting
confidence: 82%
“…The first hint that complement pathways also played a role in regulation of the initiation of the adaptive immune response to inhaled allergens came from a genetic/genomic study aimed at identifying asthma susceptibility genes in mice (25). Contrary to the previously known pro-allergic role of C5, these studies showed that susceptibility to allergen-driven AHR was linked to a loss-of-function mutation in C5.…”
Section: Role Of C5/c5a In Regulating Adaptive Immune Response To Allmentioning
confidence: 99%
“…10 Moreover, the Ifi202 gene was identified in expression studies of a congenic strain for the Nba2 locus in the NZB/NZW model of SLE. 11 Also, the importance of the complement component C5 in a model for asthma 12 and the CD36 gene for insulin resistance was demonstrated by the same technique. 13 In these experiments the global gene expression was studied and subsequently the QTL gene identified.…”
Section: Introductionmentioning
confidence: 92%
“…Microarrays of multiple allergens have been used for detection of allergenspecific IgE in patient samples (53). Expression studies of pulmonary genes helped identify the complement factor 5 locus as a susceptibility gene for allergeninduced asthma in a mouse model (54). Oligonucleotide probe microarrays were used to study the complete transcript of human mast cells thereby identifying selective expression of 89 transcripts that may be important in allergic inflammation (55).…”
Section: Computational Tools For the Study Of Allergensmentioning
confidence: 99%